QARAQALPAQ TILINIŃ TÚSINDIRME SÓZLIGINDE ANTONIMLERDIŃ BERILIWI - Mambetmuratova, M.T. (SCIENCE and SOCIETY, 2022)
The article talks about bringing antonyms in the explanatory dictionary of the Karakalpak language and analyzes their explanation.